Effects of the INSIGHT Obesity Preventive Intervention on Reported and Observed Infant Temperament. Issue 9 (December 2018) - Anzman-Frasca, Stephanie; Paul, Ian M.; Moding, Kameron J.; Savage, Jennifer S.; Hohman, Emily E.; Birch, Leann L.
ABSTRACT: Objective: Infants higher on negative reactivity and lower on regulation, aspects of temperament, have increased obesity risk. Responsive parenting (RP) has been shown to impact the expression of temperament, including the developing ability to regulate negative emotions. The aim of this analysis was to test the effects of the INSIGHT study's RP intervention designed for the primary prevention of obesity on reported and observed infant negativity and regulation. Methods: The sample included 240 mother-infant dyads randomized 2 weeks after birth to the RP intervention or a safety control intervention. Both groups received 4 home visits during the infant's first year. In the RP group, nurses delivered RP guidance in domains of sleep, feeding, soothing, and interactive play. At 1 year, mother-reported temperament was measured by a survey, and a frustration task was used to observe temperament in the laboratory. Effects of the RP intervention were tested using general linear models. Results: The RP intervention reduced overall reported infant negativity, driven by lower distress to limitations ( p < 0.05) and faster recovery from distress ( p < 0.01) in the RP group versus controls. There were no intervention effects on reported regulation or observed negativity. The intervention did increase observed regulation, particularly the use of self-comforting strategies ( p < 0.05) during the frustration task. Discussion: An RP intervention designed for early obesity prevention affected reported infant negativity and observed regulation, outcomes that have been linked with subsequent healthy development. Interventions grounded in an RP framework have the potential for widespread effects on child health and well-being.